Carbon nano tube reinforced polymer modifying and flooding agent as well as preparation method and application thereof
By using carbon nanotubes to enhance polymer mixing agent in high-temperature and high-salt environments, and regulating reservoir runners with its self-repair characteristics, the problem of poor stability of polymer dispersed glue is solved, and the water flooding efficiency and recovery rate are improved.
Patent Information
- Application Number
- CN202310784423.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing polymer dispersed glue has poor stability in high-temperature and high-salt environments and cannot maintain effective control of the advantageous flow channel for a long time.
Carbon nanotube reinforced polymer mixing agent is used to react in situ on the interpenetrating network structure by polyethylene glycol, carbon nanotubes and acrylamide. It has fracture-supplemented reversible self-healing characteristics and can be used in high temperature and high salt environments. Maintain stability.
Under high temperature and high salt conditions, carbon nanotube-enhanced polymer mixing agent achieves effective regulation of reservoir runners, improves the impact volume and recovery rate of water-driving reservoirs, and significantly improves the water control and oil increase effect.
Smart Images

Figure CN119220234A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flow channel adjustment of oil reservoirs, and in particular relates to a carbon nanotube-enhanced polymer flow adjustment agent and a preparation method and application thereof. Background Art
[0002] Water-driven oil reservoirs account for more than 80% of my country's oil reservoirs. The dominant flow channels formed by long-term scouring of injected water lead to low water drive sweep efficiency. Under the extreme water content conditions of oil wells, the recovery rate of oil reservoirs is only about 30%, and a large amount of crude oil is not recovered. Controlling the dominant flow channels and expanding the swept volume of injected water are the main and effective strategies for controlling water and increasing oil production in water-driven oil reservoirs.
[0003] At present, the main method is to inject foam, weak gel, gel dispersion, colloidal dispersion, pre-crosslinked particles, polymer microspheres and polymer dispersion into water injection wells to control the dominant flow channel. Foam has good fluidity control ability, can increase injection pressure and improve liquid absorption profile, but the foam generation process in the formation is prone to gas channeling, and the control ability of the dominant flow channel is limited; gel dispersion, weak gel, colloidal dispersion is a polymer or monomer reacting with a crosslinker in the formation to form a gel, which is prone to filtration and matrix pollution; pre-crosslinked particles have the characteristics of water absorption and expansion, and have a good plugging effect on large pores in high water content and high recovery oil fields, but the preparation process of pre-crosslinked particles is complicated, expensive, and easy to be produced from oil wells, which affects the flow channel control effect of pre-crosslinked particles; polymer dispersion is a hydrogel prepared by ground technology and process, which has great potential application value. It is generally obtained by the reaction of hydrogel and crosslinker through dispersion polymerization, inverse suspension polymerization, inverse emulsion polymerization and inverse microemulsion polymerization. When the ambient temperature rises, the movement rate of hydrogel molecules and cross-linker molecules accelerates, the probability of intermolecular collision increases, the reaction activation energy increases, and the possibility of reaction between hydrogel and cross-linker increases, so the water absorption and expansion rate of the hydrogel will increase; when the temperature of the reaction solution continues to rise, the gelation time of the hydrogel becomes shorter and the gelation strength increases; but if the temperature is too high, the hydrogel molecules will degrade, and gel dehydration and gel breaking will occur, and the stability will be poor. Summary of the invention
[0004] In view of the problem that the polymer dispersion glue in the prior art has poor salt and temperature resistance and cannot maintain stability in a high temperature and high salt environment for a long time, the purpose of the present invention is to provide a carbon nanotube-enhanced polymer flooding agent and its preparation method and application. The carbon nanotube-enhanced polymer flooding agent provided by the present invention has a self-repairing property and can undergo a reversible reaction of breaking and replenishing, so that it can automatically repair to its original state when damaged, can maintain long-term stability in a high temperature and high salt environment, and realize effective regulation of the dominant flow channel.
[0005] One of the present inventions provides a carbon nanotube-enhanced polymer displacement agent, which includes polyethylene glycol, carbon nanotubes and polyacrylamide;
[0006] The polyethylene glycol and the carbon nanotubes form an interpenetrating network structure; the polyacrylamide is obtained by in-situ reaction of acrylamide and an initiator on the interpenetrating network structure.
[0007] According to a specific embodiment of the present invention, the mass of the carbon nanotube enhanced polymer driving agent is calculated as 100%, and the carbon nanotube enhanced polymer driving agent includes 25.8wt% to 28.2wt% polyethylene glycol, 0.65wt% to 0.9wt% carbon nanotubes and 71.1wt% to 73.5wt% polyacrylamide.
[0008] According to a specific embodiment of the present invention, the weight average molecular weight of the polyethylene glycol is 5,000 to 10,000.
[0009] According to a specific embodiment of the present invention, the carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes;
[0010] Preferably, the outer diameter of the single-walled carbon nanotube is 3 nm to 20 nm, and the length is 0.1 μm to 10 μm; and / or
[0011] The multi-walled carbon nanotubes have an outer diameter of 20 nm to 200 nm and a length of 1.0 μm to 30 μm.
[0012] According to a specific embodiment of the present invention, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and azobisisobutyramidine hydrochloride.
[0013] The second aspect of the present invention provides a method for preparing the carbon nanotube-enhanced polymer displacement agent as described in the first aspect of the present invention, which comprises the following steps:
[0014] 1) mixing the polyethylene glycol, carbon nanotubes and a solvent to obtain an interpenetrating network solution;
[0015] 2) The acrylamide, initiator and interpenetrating network solution are mixed and reacted to generate polyacrylamide in situ on the interpenetrating network structure to obtain the carbon nanotube-enhanced polymer displacement agent.
[0016] According to a specific embodiment of the present invention, in step 1), the polyethylene glycol and the heated solvent are first mixed, and then mixed with the carbon nanotubes to obtain the interpenetrating network solution;
[0017] and / or
[0018] In step 2), the reaction product obtained by the reaction is dried to obtain the carbon nanotube-enhanced polymer drive agent;
[0019] Preferably, the reaction product is dried and then crushed to obtain the carbon nanotube-enhanced polymer displacement agent having a particle size of 5 μm to 50 μm.
[0020] According to a specific embodiment of the present invention, the total mass of the polyethylene glycol, carbon nanotubes, acrylamide and initiator is 100%, the amount of the polyethylene glycol is 25.8wt% to 28.2wt%, the amount of the carbon nanotubes is 0.65wt% to 0.9wt%, the amount of the acrylamide is 70.4wt% to 72.5wt%, and the amount of the initiator is 0.7wt% to 1wt%; and / or
[0021] The total weight of the polyethylene glycol, carbon nanotubes, acrylamide, initiator and solvent is 100%, and the amount of the solvent is 72 wt % to 77.9 wt %;
[0022] Preferably, the solvent is water.
[0023] According to a specific embodiment of the present invention, the temperature of the solvent after being heated and the temperature of the reaction are independently 78° C. to 83° C.; and / or
[0024] The drying temperature is 90°C to 110°C; and / or
[0025] The reaction time is 5 to 7 hours;
[0026] Preferably, the reaction is carried out in an oxygen-free, sealed environment;
[0027] Preferably, the temperature of the solvent after being heated is 80° C.; and / or
[0028] The temperature of the reaction is 80°C to 83°C.
[0029] Application of the carbon nanotube-enhanced polymer flooding agent according to one of the present inventions or the carbon nanotube-enhanced polymer flooding agent prepared by the method according to the second present invention in flow channel regulation technology of oil reservoirs, especially in flow channel regulation technology of high temperature and high mineralization oil reservoirs;
[0030] Preferably, the high temperature is not less than 110°C; and / or the high mineralization is not less than 200000 mg / L. Beneficial effects of the present invention:
[0031] In view of the problem that the polymer dispersion glue in the prior art has poor salt and temperature resistance and cannot remain stable in a high temperature and high salt environment for a long time, the present invention provides a carbon nanotube-enhanced polymer flooding agent and its preparation method and application. The carbon nanotube-enhanced polymer flooding agent is obtained by reacting acrylamide and an initiator without adding a small molecule cross-linking agent, and in situ generating polyacrylamide on an interpenetrating network structure composed of polyethylene glycol and carbon nanotubes. The carbon nanotube-enhanced polymer flooding agent can undergo a reversible self-repairing process of breaking and replenishing, has good stability under high temperature and high salt conditions, has a temperature resistance of not less than 110°C, and has a salt resistance of not less than 200,000 mg / L. Specifically, the carbon nanotube-enhanced polymer flooding agent and the mineralization degree is 5.0×10 4 mg / L to 21.0×10 4 After the hydrogel prepared from brine with a concentration of 100 mg / L was aged at 120°C for 30 days, the flow turning pressure of the hydrogel reached 850 kPa; the carbon nanotube-enhanced polymer flooding agent and the mineralization degree were 25.0×10 4 After the hydrogel prepared from the brine with a concentration of 1.0 mg / L was aged at 120°C for 30 days, the flow turning pressure of the hydrogel reached 820 kPa; the carbon nanotube-enhanced polymer flooding agent and the mineralization degree were 21.0×10 4 After being aged at 120°C for 10 days, a hydrogel with a mass fraction of 0.2 wt% of a carbon nanotube-enhanced polymer flooding agent prepared from brine with a concentration of 1.5 mg / L was injected with 0.2 PV at a temperature of 120°C, which increased the crude oil recovery by 20.2%. It is proved that the carbon nanotube-enhanced polymer flooding agent provided by the present invention has strong rigidity under high temperature and high salt conditions, and can effectively control the heterogeneity of the oil reservoir at a low concentration of 0.2 wt%, adjust the water drive flow channel well, increase the swept volume of the water drive reservoir and the recovery rate of the water drive, and achieve a significant effect of controlling water and increasing oil. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The scanning electron microscope image of the carbon nanotube-enhanced polymer displacement agent prepared in Example 2 is shown;
[0033] Figure 2 The self-healing process of the hydrogel further prepared by the carbon nanotube-enhanced polymer displacement agent prepared in Example 3 is shown;
[0034] Figure 3 The figure shows the regulation of water flooding by the carbon nanotube-enhanced polymer flooding agent prepared in Example 3. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.
[0036] Carbon nanotubes used in Examples 1 to 4:
[0037] Single-walled carbon nanotubes, industrial grade, with specifications: outer diameter 3 to 20nm, length 0.1 to 10μm.
[0038] Multi-walled carbon nanotubes, industrial grade, with specifications of: outer diameter 20 to 200nm, length 1.0 to 30μm.
[0039] Example 1
[0040] 1) Heat 100 mL of distilled water to 80° C., add 8 g of polyethylene glycol with a weight average molecular weight of 5000, stir until completely dissolved, add 0.2 g of single-walled carbon nanotubes while stirring, mix well, and obtain an interpenetrating network solution;
[0041] 2) Add 20 g of acrylamide and 0.2 g of azobisisobutyronitrile to the obtained interpenetrating network solution, pass nitrogen to deoxygenate for 15 min, seal, heat to 80° C., react for 5 h, dry the obtained reaction product at 100° C., and grind to obtain a single-walled carbon nanotube-enhanced polymer drive agent with a particle size of 5 to 50 μm.
[0042] Example 2
[0043] 1) Heat 100 mL of distilled water to 80° C., add 9 g of polyethylene glycol with a weight average molecular weight of 7500, stir until completely dissolved, add 0.3 g of multi-walled carbon nanotubes while stirring, mix well, and obtain an interpenetrating network solution;
[0044] 2) Add 25 g of acrylamide and 0.3 g of azobisisoheptonitrile to the obtained interpenetrating network solution, pass nitrogen to deoxygenate for 15 min, seal, heat to 82° C., react for 6.5 h, dry the obtained reaction product at 90° C., and grind to obtain a multi-walled carbon nanotube-enhanced polymer drive agent with a particle size of 5 to 50 μm.
[0045] Example 3
[0046] 1) Heat 100 mL of distilled water to 80° C., add 10 g of polyethylene glycol with a weight average molecular weight of 10,000, stir until completely dissolved, add 0.3 g of multi-walled carbon nanotubes while stirring, mix well, and obtain an interpenetrating network solution;
[0047] 2) Add 28 g of acrylamide and 0.4 g of azobisisobutylamidine hydrochloride to the obtained interpenetrating network solution, pass nitrogen to deoxygenate for 15 min, seal, heat to 83° C., react for 7 h, dry the obtained reaction product at 110° C., and grind to obtain a multi-walled carbon nanotube-enhanced polymer drive agent with a particle size of 5 to 50 μm.
[0048] Example 4
[0049] 1) Heat 100 mL of distilled water to 80° C., add 10 g of polyethylene glycol with a weight average molecular weight of 10,000, stir until completely dissolved, then add 0.10 g of single-walled carbon nanotubes and 0.15 g of multi-walled carbon nanotubes while stirring, and mix well to obtain an interpenetrating network solution;
[0050] 2) Add 28 g of acrylamide and 0.4 g of azobisisobutylamidine hydrochloride to the obtained interpenetrating network solution, pass nitrogen to deoxygenate for 15 min, seal, heat to 83° C., react for 7 h, dry the obtained reaction product at 110° C., and grind to obtain a multi-walled carbon nanotube-enhanced polymer drive agent with a particle size of 5 to 50 μm.
[0051] Experimental evaluation
[0052] 1. Characterization of microstructure of carbon nanotube-enhanced polymer displacement agent
[0053] The microscopic morphology of the carbon nanotube-enhanced polymer displacement agent prepared in Examples 1 to 4 was observed using a scanning electron microscope. Here, the carbon nanotube-enhanced polymer displacement agent prepared in Example 2 is taken as an example for detailed description.
[0054] Figure 1 This is a scanning electron microscope image of the carbon nanotube-enhanced polymer displacement agent prepared in Example 2. Overall, the surface of the carbon nanotube-enhanced polymer displacement agent presents a dense network structure; the carbon nanotubes are dispersed in the network space of the gel to form an interpenetrating network structure. The above shows that polyethylene glycol and carbon nanotubes form a dynamically cross-linked interpenetrating network structure.
[0055] The carbon nanotube-enhanced polymer drive agents prepared in Examples 1, 3, and 4 can be observed under a scanning electron microscope. Figure 1 The microscopic morphology is similar to that of the carbon nanotube-enhanced polymer displacement agent prepared in Example 2: the surface presents a dense network structure; the carbon nanotubes are dispersed in the network space of the gel to form an interpenetrating network structure, that is, the polyethylene glycol and the carbon nanotubes form a dynamically cross-linked interpenetrating network structure.
[0056] 2. Performance evaluation of carbon nanotube-enhanced polymer flooding agent
[0057] The salt water with different mineralizations used in the following experiments: Sodium chloride, water-soluble calcium salt and water-soluble magnesium salt were dissolved in deionized water to prepare the following five salt waters with different mineralizations:
[0058] 1# brine: total mineralization is 5.0×10 4 mg / L, of which Ca 2+ and Mg 2+ The total concentration is 0.1×10 4 mg / L;
[0059] 2# brine: total mineralization is 10.0×10 4 mg / L, of which Ca 2+ and Mg 2+ The total concentration is 0.3×10 4 mg / L;
[0060] 3# brine: total mineralization is 15.0×10 4 mg / L, of which Ca 2+ and Mg 2+ The total concentration is 0.5×10 4 mg / L;
[0061] 4# brine: total mineralization is 21.0×10 4 mg / L, of which Ca 2+ and Mg 2+ The total concentration is 2×10 4 mg / L;
[0062] 5# brine: total mineralization is 25.0×10 4 mg / L, of which Ca 2+ and Mg 2+ The total concentration is 2.5×10 4 mg / L.
[0063] A. Evaluation of the flow diversion performance of carbon nanotube-enhanced polymer displacement agents
[0064] The flow diversion performance of the carbon nanotube-enhanced polymer displacement agent was evaluated by measuring the diversion pressure of the carbon nanotube-enhanced polymer displacement agent prepared in Examples 1 to 4.
[0065] (1) 120℃, 5.0×10 4 mg / L to 21.0×10 4 Determination of flow diversion performance of carbon nanotube-enhanced polymer flooding agent under mg / L conditions
[0066] a. Preparation of hydrogel
[0067] Four portions of carbon nanotube-enhanced polymer displacement agent of equal weight were taken and placed in 1#, 2#, 3# and 4# brine respectively to obtain four hydrogels with a carbon nanotube-enhanced polymer displacement agent mass fraction of 0.2wt%, and aged at 120°C for 30 days for use;
[0068] b. Steering pressure measurement
[0069] At an injection rate of 0.3 mL / min, the four aged hydrogels were respectively passed through three layers of 80-mesh screens to simulate the porous medium and shear process of the formation. Since the carbon nanotube-enhanced polymer displacement agent absorbs liquid and swells after being placed in brine, the size of the hydrogel formed after expansion is larger than the diameter of the three overlapping layers of 80-mesh screens, causing the hydrogel to accumulate on the screen. When the displacement pressure reaches a certain value, the hydrogel can pass through the screen. The corresponding displacement pressure is called the steering pressure.
[0070] According to the above steps a and b, the turning pressures of the carbon nanotube-enhanced polymer displacement agents prepared in Examples 1 to 4 were measured respectively. The specific data are shown in Table 1.
[0071] Table 1. Steering pressure of carbon nanotube-enhanced polymer displacement agents prepared in Examples 1 to 4
[0072]
[0073] Table 1 shows that the carbon nanotube-enhanced polymer displacement agent prepared in Examples 1 to 4 has a mineralization degree of 5.0×10 4 mg / L to 21.0×10 4 After aging for 30 days at 120°C, the turning pressure of the hydrogel prepared by using 100 mg / L brine was 760 to 853 kPa. It was proved that the carbon nanotube-enhanced polymer flooding agent prepared in Examples 1 to 4 had excellent salt resistance and strong rigidity, and could effectively regulate the flow channel of the reservoir, improve the liquid absorption profile of the reservoir, increase the swept volume of water flooding, and achieve water control and oil increase.
[0074] (2) 120°C, 21.0×10 4 mg / L to 25.0×10 4 Determination of flow diversion performance of carbon nanotube-enhanced polymer flooding agent under mg / L conditions
[0075] i. Preparation of hydrogels: Weigh two equal parts of the carbon nanotube-enhanced polymer displacement agents prepared in Examples 3 and 4, respectively, and place them in 4# and 5# salt water to obtain four types of hydrogels with a carbon nanotube-enhanced polymer displacement agent mass fraction of 0.2 wt%, and age them at 120° C. for 30 days for later use;
[0076] ii. At an injection rate of 0.3 mL / min, the four aged hydrogels were respectively passed through three layers of 80-mesh sieves to simulate the porous medium and shear process of the formation, and the steering pressures of the carbon nanotube-enhanced polymer displacement agents prepared in Examples 3 and 4 were obtained as shown in Table 2.
[0077] Table 2. Steering pressure of carbon nanotube-enhanced polymer displacement agents prepared in Examples 3 and 4
[0078]
[0079] The data in Table 2 show that the carbon nanotube-enhanced polymer flooding agent prepared in Examples 3 and 4 has a mineralization of 21.0×10 4 mg / L to 25.0×10 4 After aging for 30 days at 120°C, the turning pressure of the hydrogel further prepared with brine containing 100 mg / L of sodium bicarbonate was still 736 to 832 kPa, which proves that the carbon nanotube-enhanced polymer flooding agent provided by the present invention still has strong rigidity under high temperature and ultra-high salinity, can effectively regulate the flow channel of the oil reservoir, improve the liquid absorption profile of the reservoir, greatly increase the water drive swept volume, and control water and increase oil.
[0080] B. Evaluation of the self-healing performance of carbon nanotube-enhanced polymer displacement agent cut-off-self-healing
[0081] The cut-off-self-healing performance of the carbon nanotube-enhanced polymer displacement agent prepared in Example 3 was evaluated according to the following method:
[0082] 1) Preparation of hydrogel: placing the carbon nanotube-enhanced polymer displacement agent prepared in Example 3 in 4# salt water to obtain a hydrogel with a mass fraction of 0.2 wt% of the carbon nanotube-enhanced polymer displacement agent, and aging at 120° C. for 30 days for use;
[0083] 2) The prepared hydrogel was cut into two halves, the cut surfaces of the two halves of the hydrogel were connected together, a slight stress was applied to the connected parts to make them in close contact, and then they were immersed in a 4# saline solution. After standing for 20 minutes, the final self-healing was observed.
[0084] Figure 2 The results reflect the cutting-self-healing of the hydrogel further prepared by using the carbon nanotube-enhanced polymer displacement agent prepared in Example 3. According to the order of (a), (b), (c), and (d), it can be seen that the two halves of the hydrogel reconnected by the cut surface after cutting undergo a self-healing process after being immersed in salt water, and the two halves of the hydrogel cannot be separated again by folding the cross section or pulling in two opposite directions, indicating that the hydrogel has excellent self-healing performance after cutting-self-healing.
[0085] It was verified by the same method that after the hydrogel further prepared by using the carbon nanotube-enhanced polymer drive agent prepared in Example 1, 2 or 4 was cut, the two halves of the hydrogel reconnected at the cut surface underwent a self-healing process after being immersed in salt water. The two halves of the hydrogel could not be separated again by folding the cross section or pulling in two opposite directions, and the hydrogel also had excellent self-healing properties.
[0086] C. Determination of injectability and water control and oil-increasing performance of carbon nanotube-enhanced polymer displacement agent
[0087] The following simulation experiment was conducted using the carbon nanotube-enhanced polymer displacement agent prepared in Example 3 to evaluate the injectability and water control and oil-increasing performance of the carbon nanotube-enhanced polymer displacement agent prepared in Example 3.
[0088] Artificial three-layer heterogeneous core: Gas testing permeability is 1000 / 3000 / 5000mD, average porosity is 26.7%, and original oil saturation is 26.7%;
[0089] Crude oil: viscosity 20.3 mPa·s;
[0090] Aging hydrogel: First, the carbon nanotube-enhanced polymer displacement agent prepared in Example 3 was dried and crushed into particles of 5 to 20 μm, and then placed in 4# salt water to obtain a hydrogel with a mass fraction of 0.2 wt% of the carbon nanotube-enhanced polymer displacement agent, and aged for 10 days at 120° C. in a sealed condition for use;
[0091] Follow the steps below to conduct a simulation experiment at 120°C with a fixed injection rate of 0.5 mL / min throughout the process:
[0092] (1) Perform a water flooding on the artificial three-layer heterogeneous core until no oil is produced, and record the changes of injection pressure, water content, and cumulative recovery factor with injected pore volume during the water flooding process;
[0093] (2) Then, 0.2 PV of hydrogel was injected into the artificial three-layer heterogeneous core after the first water flooding for polymer flooding, and finally a second water flooding was performed. The changes in injection pressure, water content, and cumulative recovery as a function of injected pore volume during the polymer flooding and the second water flooding were recorded.
[0094] For details, see Figure 3 .
[0095] Figure 3 This shows the simulation experiment of further preparing the carbon nanotube-enhanced polymer displacement agent prepared in Example 3 into a hydrogel. Figure 3It can be seen that due to the strong heterogeneity of the core, the recovery rate of the first water flooding is low, only 35%; after injecting 0.2PV of hydrogel, the injection pressure rises, indicating that the carbon nanotube-enhanced polymer flooding agent prepared in Example 3 has good injectability and propagation properties; the injection pressure in the secondary water flooding stage further increases, proving that the hydrogel further prepared by the carbon nanotube-enhanced polymer flooding agent prepared in Example 3 has entered the high permeability layer during the polymer flooding process of the simulation experiment, and exhibits excellent anti-scouring performance. After injecting 0.2PV of hydrogel further prepared by the carbon nanotube-enhanced polymer flooding agent prepared in Example 3, the crude oil recovery rate increased by 20.2%. The above experimental results show that the carbon nanotube-enhanced polymer flooding agent prepared in Example 3 has good performance at low concentration (specifically 0.2wt%) and high mineralization (specifically 21.0×10 4 mg / L) and high temperature (specifically 120°C), the water drive flow channel can be well adjusted, and the effect of controlling water and increasing oil is significant.
[0096] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.
Claims
1. A carbon nanotube enhanced polymer displacement agent comprising polyethylene glycol, carbon nanotubes and polyacrylamide; The polyethylene glycol and the carbon nanotubes form an interpenetrating network structure; the polyacrylamide is obtained by in-situ reaction of acrylamide and an initiator on the interpenetrating network structure.
2. The carbon nanotube-enhanced polymer displacement agent according to claim 1, characterized in that: The mass of the carbon nanotube-enhanced polymer displacement agent is calculated as 100%, and the carbon nanotube-enhanced polymer displacement agent includes 25.8 wt % to 28.2 wt % of polyethylene glycol, 0.65 wt % to 0.9 wt % of carbon nanotubes, and 71.1 wt % to 73.5 wt % of polyacrylamide.
3. The carbon nanotube-enhanced polymer displacement agent according to claim 1 or 2, characterized in that: The weight average molecular weight of the polyethylene glycol is 5,000 to 10,000.
4. The carbon nanotube-enhanced polymer displacement agent according to any one of claims 1 to 3, characterized in that: The carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
5. The carbon nanotube-enhanced polymer displacement agent according to any one of claims 1 to 4, characterized in that: The initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile and azobisisobutyramidine hydrochloride.
6. A method for preparing the carbon nanotube-enhanced polymer displacement agent according to any one of claims 1 to 5, comprising the following steps: 1) mixing the polyethylene glycol, carbon nanotubes and a solvent to obtain an interpenetrating network solution; 2) The acrylamide, initiator and interpenetrating network solution are mixed and reacted to generate polyacrylamide in situ on the interpenetrating network structure to obtain the carbon nanotube-enhanced polymer displacement agent.
7. The method according to claim 6, characterized in that In step 1), the polyethylene glycol and the heated solvent are first mixed, and then mixed with the carbon nanotubes to obtain the interpenetrating network solution; and / or In step 2), the reaction product obtained by the reaction is dried to obtain the carbon nanotube-enhanced polymer drive control agent.
8. The method according to claim 6 or 7, characterized in that: The total weight of the polyethylene glycol, carbon nanotubes, acrylamide and initiator is 100%, the amount of the polyethylene glycol is 25.8wt% to 28.2wt%, the amount of the carbon nanotubes is 0.65wt% to 0.9wt%, the amount of the acrylamide is 70.4wt% to 72.5wt%, and the amount of the initiator is 0.7wt% to 1wt%; and / or The total weight of the polyethylene glycol, carbon nanotubes, acrylamide, initiator and solvent is 100%, and the amount of the solvent is 72 wt % to 77.9 wt %; Preferably, the solvent is water.
9. The method according to claim 7 or 8, characterized in that: The temperature of the heated solvent and the temperature of the reaction are independently 78°C to 83°C; and / or The drying temperature is 90°C to 110°C; and / or The reaction time is 5 to 7 hours; Preferably, the reaction is carried out in an oxygen-free, sealed environment.
10. Application of the carbon nanotube-enhanced polymer flooding agent according to any one of claims 1 to 5 or the carbon nanotube-enhanced polymer flooding agent prepared by the method according to any one of claims 6 to 9 in flow channel regulation technology of oil reservoirs, especially in flow channel regulation technology of high temperature and high salinity oil reservoirs; Preferably, the high temperature is not less than 110° C.; and / or the high mineralization is not less than 200,000 mg / L.
Citation Information
Patent Citations
Preparation method of aerogel based on double network structure design
CN108192153A
Hydroxylated multi-dimensional nano-material hybrid dispersion gel and application thereof
CN110776608A
Carbon nanotube hybrid pre-crosslinked gel particles for deep profile control and flooding of oil reservoir and preparation method thereof
CN111533863A
Profile control and flooding agent for oil reservoirs and preparation method thereof
CN111763505A
Aqueous two-phase polyacrylamide terpolymer nano microsphere latex and preparation method thereof
CN112341570A
